2020
DOI: 10.3168/jds.2020-18619
|View full text |Cite
|
Sign up to set email alerts
|

Heat treatment of bovine colostrum: II. Effects on calf serum immunoglobulin, insulin, and IGF-I concentrations, and the serum proteome

Abstract: In-depth analysis of colostrum components has identified hundreds of proteins, but data are sparse regarding their systemic uptake in the newborn calf. Moreover, heat treatment may influence these colostral components and their absorption. Our objectives were to describe the serum proteome of newborn calves before and after colostrum feeding and the possible effects of colostral heat treatment. Newborn Holstein heifer calves (n = 22) were randomized within pair and fed heat-treated (n = 11; 60°C, 60 min) or ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 48 publications
(80 reference statements)
0
13
0
Order By: Relevance
“…Zhang et al [64] identified 212 different types of proteins in the colostrum and milk proteome of four cows and quantified 208 of the identified proteins. Mann et al [65] identified 663 different kinds of proteins, while using proteomics techniques to evaluate the serum proteins with a low abundance in newborn calves. However, although Mann et al [65] measured IgG using RID, the authors did not quantify IgG using the proteome.…”
Section: Proteomicsmentioning
confidence: 99%
“…Zhang et al [64] identified 212 different types of proteins in the colostrum and milk proteome of four cows and quantified 208 of the identified proteins. Mann et al [65] identified 663 different kinds of proteins, while using proteomics techniques to evaluate the serum proteins with a low abundance in newborn calves. However, although Mann et al [65] measured IgG using RID, the authors did not quantify IgG using the proteome.…”
Section: Proteomicsmentioning
confidence: 99%
“…Indeed, viability was reduced but not completely eliminated after pasteurizing for 60 min at 60°C. Also the authors state that although viability of colostral immune cells is reduced, more research is required regarding functionality and biological meaning of colostral cells ( 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…We summarized the results of the existing literature in Supplementary Table 1. The majority of studies show that colostral IgG concentration is not (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53) or only slightly affected (54-57) by heating at <60 • C for either 30 or 60 min. In contrast, heating of colostrum above 60 • C frequently resulted in significant loss of colostral IgG (41-48, 50, 54, 58-60).…”
Section: Pasteurizing Colostrummentioning
confidence: 99%
“…This observation can be explained by the heat stability of different proteins. In general, the heating of colostrum results in a change in the solubility of almost all whey proteins, an effect that can be observed at temperatures as low as 40°C [35,36]. Gradual denaturation of proteins occurs at temperatures of 60°C and higher due to the destruction of the secondary or tertiary structure caused by the dissolution of non-covalent bonds [37].…”
Section: Discussionmentioning
confidence: 99%